2007
DOI: 10.1071/wf06079
|View full text |Cite
|
Sign up to set email alerts
|

Firebrand generation from burning vegetation

Abstract: A series of real-scale fire experiments were performed to determine the size and mass distribution of firebrands generated from Douglas-fir (Pseudotsuga menziesii) trees. The experiments were performed in the Large Fire Laboratory at the National Institute of Standards and Technology. The Douglas-fir trees used for the experiments ranged in total height from 2.6 to 5.2 m and the tree moisture content was varied. An array of pans filled with water was used to collect the firebrands that were generated from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
81
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 128 publications
(90 citation statements)
references
References 2 publications
6
81
0
Order By: Relevance
“…Regarding ornamental vegetation, Long et al (2006a) provided flammability data for horticultural beds by evaluating the effect of the type of mulch, planting composition and drought conditions on fire spread and heat release in both field and controlledenvironment conditions. Several experiments were carried out on firebrands but very few used surface fuels (Manzello et al 2006a(Manzello et al , 2006b(Manzello et al , 2007(Manzello et al , 2008(Manzello et al , 2009Ganteaume et al 2011b). …”
mentioning
confidence: 99%
“…Regarding ornamental vegetation, Long et al (2006a) provided flammability data for horticultural beds by evaluating the effect of the type of mulch, planting composition and drought conditions on fire spread and heat release in both field and controlledenvironment conditions. Several experiments were carried out on firebrands but very few used surface fuels (Manzello et al 2006a(Manzello et al , 2006b(Manzello et al , 2007(Manzello et al , 2008(Manzello et al , 2009Ganteaume et al 2011b). …”
mentioning
confidence: 99%
“…Manzello et al [5] have shown that the firebrands produced using these filtering and ignition procedures generate firebrands with mass up to 0.2 g and surface area up to 1000 mm 2 . This is within the range of firebrands generated from burning conifer species (Douglas-Fir and Korean Pine Trees) [8][9].…”
Section: Nist Firebrand Generator (Nist Dragon)mentioning
confidence: 99%
“…Researchers have tried to understand the phenomenology of fire-spotting through both experimental and theoretical aspects to update the existing wildfire management decision support systems. Most of the experimental procedures for studying the fire-spotting phenomenon focus on characterization of the gen-5 eration of firebrands (Manzello et al, 2007;El Houssami et al, 2016;Thomas et al, 2017), shape and size of the firebrands (Manzello et al, 2009;Tohidi et al, 2015), drag forces and ignition processes (Manzello et al, 2008). The short temporal and spatial scales of the experiments limit a detailed description of the landing distributions and the flight paths of the firebrands.…”
Section: Introductionmentioning
confidence: 99%